DAMPAK PERUBAHAN HARGA BAHAN BAKAR MINYAK (BBM) TERHADAP NILAI TUKAR PETANI (NTP) DI PROVINSI SULAWESI UTARA - Muhammad R. Ipango; Eyverson ., Ruauw; Nootje M. Benu (Sam Ratulangi University, 2017)
This study aims to determine the impact of changes in increasing fuel price on Farmers Exchange Rate (NTP) in North Sulawesi Province. This study uses secondary data, mainly from the Central Bureau of Statistics (BPS) of North Sulawesi. Data collection was conducted for four months, from December 2016 until April 2017. The data used in this research is data from 2013 until 2016. The research method used in this research is descriptive research. The results showed that with the increase of Fuel Oil price is one of the factors that influence the Farmer's Farmer's Exchange Rate (NTP) as a whole by increasing the cost of household consumption, agricultural production cost, transportation cost, and transportation cost